Photoresponse of a La1.85Sr0.15CuO4 nanostrip. (25th May 2017) - Shibata, Hiroyuki; Kirigane, Naoto; Fukao, Kentaro; Sakai, Daisuke; Karimoto, Shinichi; Yamamoto, Hideki
Abstract: We report on the fabrication and photoresponse of a 5 nm thick La1.85 Sr0.15 CuO4 nanostrip with a width of 100 nm. The I–V characteristics of the nanostrip show a hysteresis and a sharp voltage jump at critical current ( I c ). The critical current density J c (3 K) of the nanostrip is 2.3 × 10 7 A cm −2 . The nanostrip exhibits photoresponse signals when illuminated by a pulse laser at 1560 nm wavelength with a bias current just below I c . The height of the signal reduces as the optical intensity decreases, and disappears below −10 dBm. The signal also decreases as the temperature increases, but it exists up to 30 K. These results suggest the possibility of using the La1.85 Sr0.15 CuO4 nanostrip as a single-photon detector working at high temperature by further reducing the cross-section of the strip.